Inhibition of biofilm formation in Mycobacterium smegmatis by Parinari curatellifolia leaf extracts - Benjamin Bhunu; Ruvimbo Mautsa; Stanley Mukanganyama (BMC, 2017)
Abstract Background Tuberculosis (TB) is a serious public health problem worldwide. Mycobacterium tuberculosis (M. tuberculosis) grows as drug tolerant pellicles. Agents that inhibit biofilm formation in M. tuberculosis have the potential to reduce the disease treatment period and improve the quality of tuberculosis chemotherapy. Parinari curatellifolia (P. curatellifolia) leaf extracts are claimed to treat symptoms similar to tuberculosis in ethnomedicinal practices. Mycobacterium smegmatis (M. smegmatis) is a surrogate organism used in antimycobacterial drug discovery assays. In this study, the effect of the leaf extracts of P. curatellifolia on M. smegmatis growth and biofilm formation was investigated in order to determine the basis of its use in traditional medicinal use. Methods Phytochemicals from P. curatellifolia leaves were prepared using a mixture of 50% dichloromethane (DCM): 50% methanol and by serial exhaustive extraction using different solvents of decreasing polarity. The solvents were used in the following order, hexane > dichloromethane > ethyl acetate > acetone >ethanol > methanol > water. The micro-broth dilution method was used as an antimycobacterial susceptibility test to screen for the extract that effectively inhibited M. smegmatis growth and biofilm formation. Biofilm quantification was performed by staining the biofilms with crystal violet and determining the amount of the stain using a spectrophotometer. In addition, the effects of combining the most active extract with kanamycin were also investigated. Results The minimum inhibitory concentrations (MIC) of the extracts were found to be 6.2 μg/ml for the acetone extract, 12.5 μg/ml for both the ethanol and the total extract and 50 μg/ml for both the methanol and ethyl acetate extracts. The ethanol extract, dichloromethane extract and water extract were the only extracts that effectively inhibited biofilm formation in M. smegmatis. Combining the ethanol extract with kanamycin enhanced the effect of the ethanol extract in terms of inhibition of biofilm formation. Conclusions P. curatellifolia leaves contain phytochemicals that have the potential to be used both as antimycobacterial and anti-biofilm formation compounds.